Pengaruh Sosialisasi Perpajakan dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak: Studi pada Pelaku UMKM yang Bergerak di Bidang Coffee Shop - Miranda, Alissa; Setiawan, Mia Angelina (Universitas Negeri Padang, 2025)
This study aims to examine the influence of tax socialization and tax understanding on the compliance of Micro Small and Medium Sized Enterprise taxpayers engaged in the coffee shop sector. The population in this study is Micro Small and Medium Sized Enterprise taxpayers who own coffee shops in Pekanbaru City. Data was collected by providing questionnaires through google forms to the respondents concerned. The data analysis technique used is multiple linear regression with the help of SPSS Ver 27. The results of the study show that Tax Socialization has a positive effect on the Tax Compliance of Micro Small and Medium Sized Enterprise Taxpayers engaged in the Coffee Shop sector and Tax Understanding has a positive effect on the Tax Compliance of Micro Small and Medium Sized Enterprise Taxpayers engaged in the Coffee Shop sector.